SEASONAL IMPACT ANALYSIS ON POPULATION DUE TO CONTINUOUS SULPHUR EMISSIONS FROM SEVERONIKEL SMELTERS OF THE KOLA PENINSULA - Alexander Mahura; Iraxte Gonzalez-Aparicio; Roman Nuterman; Alexander Baklanov (Geography, Environment, Sustainability, 2018)
This study is devoted to investigation of total deposition and loading patterns for population of the North-West Russia and Scandinavian countries due to continuous emissions (following “mild emission scenario”) of sulphates from the Cu-Ni smelters (Severonikel enterprise, Murmansk region, Russia). The Lagrangian long-range dispersion model (Danish Emergency Response Model for Atmosphere) was run in a long-term mode to simulate atmospheric transport, dispersion and deposition over the Northern Hemispheric’s domain north of 10°N, and results were integrated and analyzed in the GIS environment. Analysis was performed on annual and seasonal scales, including depositions, impact on urban areas and calculating individual and collective loadings on population in selected regions ofRussiaand Scandinavian countries.It was found that wet deposition dominates, and it is higher in winter. The North-West Russia is more influenced by the Severonikel emissions compared with the Scandinavian countries. Among urban areas, the Russian cities ofMurmansk(due to its proximity to the source) andArkhangelsk(due to dominating atmospheric flows) are under the highest impact. The yearly individual loadings on population are the largest (up to 120 kg/person) for theMurmanskregion; lower (15 kg/person) for territories of the northernNorway, and the smallest (less than 5 kg/person) for the easternFinland,KareliaRepublic, andArkhangelskregion. These loadings have distinct seasonal variability with a largest contribution during winter-spring for Russia, spring – for Norway, and autumn – for Finland and Sweden; and the lowest during summer (i.e. less than 10 and 1 kg/person for the Russia and Scandinavian countries, respectively). The yearly collective loadings for population living on the impacted territories inRussia,Finland,Norway, and Swedenare 2628, 140.4, 13, and 10.7 tonnes, respectively.